Health behavior, health, and socioeconomic background in adolescence as risk factors for traumatic brain injuries: A longitudinal study - Teuho, Alisa; Vaajala, Matias; Ponkilainen, Ville; Koivusilta, Leena; Rimpelä, Arja; Mattila, Ville M. (Elsevier BV, 2025)
Introduction: Traumatic brain injuries (TBI) are a considerable health burden on adolescents and young adults. This study aims to assess the influence of health compromising behavior, poor perceived health, poor school success, and low family socioeconomic background during adolescence on subsequent TBI in a large cohort of Finnish adolescents with an average 25-year follow-up.
Materials and methods: Baseline Finnish Adolescent Health and Lifestyle survey data gathered biennially (1981–1997) was linked with the diagnosis of subsequent TBI from the Finnish Care Register for Health Care. A structural equation modeling (SEM) was used to analyze the associations between health behavior, poor perceived health, poor school success, and low family socioeconomic background during adolescence on subsequent TBI.
Results: Total of 41 336 persons were included in the analyses. During the follow-up, 1 459 (3.5 %) TBIs occurred. Men were more likely to suffer a TBI. The mean follow-up time was 25.3 years (SD 4.0) and the mean age at the time of TBI was 32.1 years (SD 7.7). Health compromising behavior and not living with both parents in adolescence were associated with the increased risk of TBI. Also, poor perceived health and stress symptoms increased the risk of TBI. Low family socioeconomic status (SES) was only indirectly associated with TBI trough health compromising behavior.
Conclusion: The main finding was that health compromising behavior was associated with TBI, and low family SES was associated with TBI through health compromising behavior in later life. Poor perceived health, stress symptoms, and not living with both parents in adolescence increased the risk of TBI, too. Our findings suggest that adolescents who are at risk of drifting into health compromising behavior and report stress symptoms have an increased risk of TBI in later life.